The Palgrave handbook of infertility in history : approaches, contexts and perspectives - Davis, Gayle, 1974-; Loughran, Tracey (Palgrave Handbooks., 2017)
This ground-breaking, interdisciplinary volume provides an overdue assessment of how infertility has been understood, treated and experienced in different times and places. It brings together scholars from disciplines including history, literature, psychology, philosophy, and the social sciences to create the first large-scale review of recent research on the history of infertility. Through exploring an unparalleled range of chronological periods and geographical regions, it develops historical perspectives on an apparently transhistorical experience. It shows how experiences of infertility, access to treatment, and medical perspectives on this 'condition' have been mediated by social, political, and cultural discourses. The handbook reflects on and interrogates different approaches to the history of infertility, including the potential of cross-disciplinary perspectives and the uses of different kinds of historical source material, and includes lists of research resources to aid teachers and researchers. It is an essential 'go-to' point for anyone interested in infertility and its history.